Crisis Management in a Collectivistic Country During the Covid-19 Pandemic - Rocha, Thelma Valéria; Bretas, Vanessa P. G.; Fonseca, Márcio; Pizani, Cássia Aparecida; Yojo, Angela Satiko (Internext, 2022)
Objective: The article aims to analyze crisis management in the franchising sector of a collectivistic country during the Covid-19 crisis. Method: The empirical research, using qualitative exploratory methods, was based on three in-depth interviews with franchising sector stakeholders, in addition to the thematic analysis of six webinars promoted by the ABF from April 15 to 28, 2020. According to Hofstede's country rating system, data collection took place in Brazil, a highly collectivistic country. Findings: Findings show that franchise chains had to rethink their relationships with various stakeholders such as customers, employees, suppliers, and the government, as collectivistic countries are more likely to value a brand’s approach to society in times of crisis. Moreover, franchisors developed alternative sales channels such as websites, and social media, among others. Additionally, what sustained those companies during the crisis was their connection with their purpose. Relevance: This study presents contributions to other companies in similar cultural settings by exploring the actions taken by the franchise chains during the crisis and identifying the best practices and paths taken by a collectivistic country. Contribution: This article contributes to investigations of the effects of the Covid-19 public health crisis in the franchising sector, one of the most relevant economic sectors, in a collectivistic country. Thus, it adds to existing franchising literature by associating a cultural trait with crisis management.